# What is the value of $4\cos {18^0} - 3\sec {18^0} - 2\tan {18^0}$.

$

{\text{a}}{\text{. 0}} \\

{\text{b}}{\text{. }}\dfrac{{\sqrt 5 - 1}}{4} \\

{\text{c}}{\text{. }}\dfrac{{\sqrt 5 + 1}}{4} \\

{\text{d}}{\text{. 1}} \\

$

Answer

Verified

365.4k+ views

Hint – In this question apply some basic properties of trigonometric identities such as $\cos 3\theta = \left( {4{{\cos }^3}\theta - 3\cos \theta } \right),{\text{ }}\sin 2\theta = 2\sin \theta \cos \theta $, to reach the solution of the problem.

Let,

$x = 4\cos {18^0} - 3\sec {18^0} - 2\tan {18^0}$

In above equation multiply both sides by ${\cos ^2}{18^0}$ , we have

$x.{\cos ^2}{18^0} = \left( {4\cos {{18}^0} - 3\sec {{18}^0} - 2\tan {{18}^0}} \right){\cos ^2}{18^0}$

Now as we know that $\sec \theta .\cos \theta = 1,{\text{ }}\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$, so use this property and simplify the above equation we have,

$\begin{gathered}

x.{\cos ^2}{18^0} = \left( {4{{\cos }^3}{{18}^0} - 3\sec {{18}^0}\cos {{18}^0}\cos {{18}^0} - 2\dfrac{{\sin {{18}^0}}}{{\cos {{18}^0}}}{{\cos }^2}{{18}^0}} \right) \\

x.{\cos ^2}{18^0} = 4{\cos ^3}{18^0} - 3\cos {18^0} - 2\sin {18^0}\cos {18^0} \\

\end{gathered} $

Now as we all know $\cos 3\theta = \left( {4{{\cos }^3}\theta - 3\cos \theta } \right),{\text{ }}\sin 2\theta = 2\sin \theta \cos \theta $, so use this property in above equation we have,

$\begin{gathered}

x.{\cos ^2}{18^0} = \cos {\left( {3 \times 18} \right)^0} - \sin \left( {2 \times {{18}^0}} \right) \\

x.{\cos ^2}{18^0} = \cos {\left( {54} \right)^0} - \sin \left( {{{36}^0}} \right) \\

\end{gathered} $

Now we know that $\cos \theta = \sin \left( {90 - \theta } \right)$, so use this property in above equation we have,

$

\Rightarrow x.{\cos ^2}{18^0} = \sin {\left( {90 - 54} \right)^0} - \sin \left( {{{36}^0}} \right) \\

\Rightarrow x.{\cos ^2}{18^0} = \sin {\left( {36} \right)^0} - \sin \left( {{{36}^0}} \right) = 0 \\

\Rightarrow x = \dfrac{0}{{{{\cos }^2}{{18}^0}}} = 0 \\

$

So this is the required answer.

Hence, option (a) is correct.

Note – In such types of questions first multiply the equation by ${\cos ^2}{18^0}$ in both sides of the equation, then convert R.H.S part of the question into standard formulas of trigonometric identities which is stated above and simplify then use the property that $\cos \theta = \sin \left( {90 - \theta } \right)$ and again simplify then we will get the required answer.

Let,

$x = 4\cos {18^0} - 3\sec {18^0} - 2\tan {18^0}$

In above equation multiply both sides by ${\cos ^2}{18^0}$ , we have

$x.{\cos ^2}{18^0} = \left( {4\cos {{18}^0} - 3\sec {{18}^0} - 2\tan {{18}^0}} \right){\cos ^2}{18^0}$

Now as we know that $\sec \theta .\cos \theta = 1,{\text{ }}\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$, so use this property and simplify the above equation we have,

$\begin{gathered}

x.{\cos ^2}{18^0} = \left( {4{{\cos }^3}{{18}^0} - 3\sec {{18}^0}\cos {{18}^0}\cos {{18}^0} - 2\dfrac{{\sin {{18}^0}}}{{\cos {{18}^0}}}{{\cos }^2}{{18}^0}} \right) \\

x.{\cos ^2}{18^0} = 4{\cos ^3}{18^0} - 3\cos {18^0} - 2\sin {18^0}\cos {18^0} \\

\end{gathered} $

Now as we all know $\cos 3\theta = \left( {4{{\cos }^3}\theta - 3\cos \theta } \right),{\text{ }}\sin 2\theta = 2\sin \theta \cos \theta $, so use this property in above equation we have,

$\begin{gathered}

x.{\cos ^2}{18^0} = \cos {\left( {3 \times 18} \right)^0} - \sin \left( {2 \times {{18}^0}} \right) \\

x.{\cos ^2}{18^0} = \cos {\left( {54} \right)^0} - \sin \left( {{{36}^0}} \right) \\

\end{gathered} $

Now we know that $\cos \theta = \sin \left( {90 - \theta } \right)$, so use this property in above equation we have,

$

\Rightarrow x.{\cos ^2}{18^0} = \sin {\left( {90 - 54} \right)^0} - \sin \left( {{{36}^0}} \right) \\

\Rightarrow x.{\cos ^2}{18^0} = \sin {\left( {36} \right)^0} - \sin \left( {{{36}^0}} \right) = 0 \\

\Rightarrow x = \dfrac{0}{{{{\cos }^2}{{18}^0}}} = 0 \\

$

So this is the required answer.

Hence, option (a) is correct.

Note – In such types of questions first multiply the equation by ${\cos ^2}{18^0}$ in both sides of the equation, then convert R.H.S part of the question into standard formulas of trigonometric identities which is stated above and simplify then use the property that $\cos \theta = \sin \left( {90 - \theta } \right)$ and again simplify then we will get the required answer.

Last updated date: 02nd Oct 2023

•

Total views: 365.4k

•

Views today: 7.65k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Who had given the title of Mahatma to Gandhi Ji A Bal class 10 social science CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

How many millions make a billion class 6 maths CBSE

Find the value of the expression given below sin 30circ class 11 maths CBSE